P-106 Can digital communication provide a social world and sense of connectivity?. Issue Volume 5: Issue (2015)Supplement 3 (1st November 2015) - McLaughlin, Kimberley
Abstract : "The experience of entering into community is more enduring than the Self" (Balfour Mount, 2012) As social animals we are biologically, cognitively, physically, and spiritually wired to love, to be loved, to belong and to be accepted; social connexion is one of our fundamental human needs (e.g. Maslow 1943, 1954). Burr (1995) suggests that our 'identity originates not from inside the person but from the social realm'. In a world of digital communication our research aimed to explore patients' experiences of connectivity; do certain kinds of communication play a role in increasing/decreasing feelings of e.g. isolation, connectivity, wellbeing and sense of identity? We hoped our findings might influence developments in hospice communication styles and services in accordance with patients' preferences. 'Unstructured' interviews with 50 patients explored the type of communication used in different contexts and within different relationships, specifically: Are there preferred contexts/types of conversations for face-to-face, landline, mobile, text, email and social networks communication? How does the relationship influence the type of communication e.g. between family, friends, neighbours, colleagues, professionals? Individual experiences and relationships with these multiple communications? Findings: Digital multimedia communications were found to be beneficial in providing a sense of connectivity and self-identity Face-to-face connectivity with neighbours and friends is reported to be rare and family face-to-face contact is often reported as infrequent. Digital communication, social networks and structured activities (e.g. hospice services) are found to be a valuable source of connectivity; patients find they can share their inner most feelings, experience decreased feelings of isolation and increased feelings of well-being. Conclusions: Hospices need to widen and develop: Communication styles with patients e.g. email, text and innovative and creative services which provide opportunities to connect with those in similar circumstances e.g. IT skills workshops for patients/carers, rehabilitation services, psychosocial therapeutic groups and activities.